2022
DOI: 10.24315/tred.908127
|View full text |Cite
|
Sign up to set email alerts
|

İş Yaşam Dengesi̇ni̇n Yordayicisi Olarak Tükenmi̇şli̇k: Türki̇ye’de Halk Eği̇ti̇mi̇ Merkezi̇ Müdürleri̇ Üzeri̇ne Bi̇r Çalişma

Abstract: Bu araştırmada halk eğitimi merkezi müdürlerinin tükenmişlik düzeyleri ile iş yaşam dengeleri arasındaki ilişkinin belirlenmesi amaçlanmıştır. Araştırmanın evreni, Türkiye genelinde görev yapan 992 halk eğitimi merkezi müdürüdür. Örneklem alma yoluna gidilmemiş ve neticede 335 halk eğitim merkezi müdürünün araştırmaya gönüllü olarak katılımı ile araştırma yürütülmüştür. Araştırma verileri Maslach Tükenmişlik Ölçeği ve İş Yaşam Dengesi Ölçeği ile toplanmıştır. Verilerin çözümlenmesinde standart sapma, aritmetik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…According to the third finding of the present study, the work-life balance of internal auditors had a significant effect on their professional burnout levels and this effect was inversely proportional. As with other relationships, this relationship was consistent with previous studies (Keeton et al, 2007;Kanwar, Singh, and Kodwani, 2009;Rama Devi and Nagini, 2013;İskender and Yaylı, 2017;Putranti, 2018;Çetinkaya and Dinçer, 2021;Batur and Saylık, 2022). The final finding of the study showed that internal auditors' work-life balance mediated the negative relationship between self-efficacy belief and professional burnout.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…According to the third finding of the present study, the work-life balance of internal auditors had a significant effect on their professional burnout levels and this effect was inversely proportional. As with other relationships, this relationship was consistent with previous studies (Keeton et al, 2007;Kanwar, Singh, and Kodwani, 2009;Rama Devi and Nagini, 2013;İskender and Yaylı, 2017;Putranti, 2018;Çetinkaya and Dinçer, 2021;Batur and Saylık, 2022). The final finding of the study showed that internal auditors' work-life balance mediated the negative relationship between self-efficacy belief and professional burnout.…”
supporting
confidence: 90%
“…Mevcut çalışmanın üçüncü bulgusuna göre, iç denetçilerin iş-yaşam dengesinin mesleki tükenmişlik düzeyleri üzerinde anlamlı etkisi vardır ve bu etki ters orantılıdır. Diğer ilişkilerde olduğu gibi bu ilişkide önceki çalışmalarla tutarlıdır (Keeton vd., 2007;Kanwar, Singh ve Kodwani, 2009;Rama Devi ve Nagini, 2013;İskender ve Yaylı, 2017;Putranti, 2018;Çetinkaya ve Dinçer, 2021;Batur ve Saylık, 2022). Çalışmanın son bulgu ise, iç denetçilerin iş-yaşam dengesinin, öz yeterlilik inancı ile mesleki tükenmişlik arasındaki negatif ilişkiye aracılık ettiğini göstermektedir.…”
Section: Sonuçunclassified
“…In the karaboğazı system, log walls are built by stacking the logs on top of each other inside the hollows created for them. Since the mosques carry the same characteristics as the houses in the area, the structures may seem to be houses at first glance [6]. The covering system of these mosques includes the rewaq on the outside and consists of a wide eaved hipped roof covered with brick in the Turkish style, locally called dört omuz çatı (a fourshouldered roof).…”
Section: Fig 2 Kurtboğazı and Karaboğazmentioning
confidence: 99%
“…In the engraving technique, the motifs in the composition are surrounded by deep grooves so that the pattern emerges as a relief. In the openwork wood technique, geometrical motifs can be seen of overlapping squares, polygonal shapes, circles, parallel, straight and bent lines, zig-zags, stars, bands, wavy lines, loops, braid motifs, basketweaves, chevrons, and pendants [6]. Naturalist decorations are dominant in the openwork and engraving techniques.…”
Section: Decorative Featuresmentioning
confidence: 99%
See 1 more Smart Citation